Prognostic impact of coexisting cardiovascular disease in patients with cancer: A multicenter retrospective cohort study - Yoshihiro Kuwabara; Toshitaka Morishima; Haruka Kudo; Chaochen Ma; Mizuki Shimadzu Kato; Shihoko Koyama; Kayo Nakata; Takahiro Tabuchi; Isao Miyashiro (Heliyon, 2024)
Background: The incidence of malignancy and cardiovascular disease (CVD) is increasing worldwide. However, it is not entirely clear how the coexistence of CVD at the time of cancer diagnosis affects the overall survival of patients with cancer. Methods and results: We used the cancer registries and administrative claims data of patients diagnosed with cancer at 36 designated cancer care hospitals in Osaka, Japan, from 2010 to 2015. The Cox proportional hazard model was used to examine how coexisting CVD (heart failure [HF], ischemic heart disease, peripheral arterial disease, cerebrovascular accidents, and atrial fibrillation) affected overall survival and the impact of HF severity, as documented by the New York Heart Association (NYHA) classification. Of the 131,701 patients with cancer, 9704 had coexisting CVD. The 3-year survival rates for patients with and without coexisting CVD were 62.9 % and 77.6 %, respectively. The adjusted hazard ratio (aHR) for all-cause mortality for coexisting CVD was 1.47 (95 % confidence interval, 1.41–1.52). Among the CVD subtype, patients with coexisting HF had the poorest prognosis. The aHRs in patients with HF by NYHA classification, using the patients without HF as a reference, were as follows: Class I: 1.33 (p = 0.217); II: 1.68 (p < 0.001); III: 1.54 (p = 0.011); IV: 2.47 (p < 0.001). Conclusion: Coexisting CVD and HF severity at cancer diagnosis is associated with survival in patients with cancer.